(untitled) (Texas Journal of Medical Science, 2021)
This article contains information about the fungal world of melons in Surkhandarya region. In this case, the most common fungal species in melons and watermelons from the main melon crops and the laws of their distribution by plants were studied. The obtained data are of theoretical importance in the protection of melon crops from fungal diseases.